Core-shell structure graphite phase carbon nitride derivative and preparation method thereof

By constructing a core-shell structure of phosphorus/boron co-doped core and phytic acid copper shell on the surface of graphite phase carbon nitride, the problems of toxicity, low efficiency and poor compatibility of traditional polymer flame retardants are solved, achieving efficient and environmentally friendly flame retardant effects and improving the thermal stability and mechanical properties of the material.

CN120737430APending Publication Date: 2025-10-03CHAOHU UNIV

Patent Information

Application Number
CN202510867589.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Traditional polymer flame retardants have problems such as the release of toxic and harmful gases, low flame retardant efficiency, poor interface compatibility and decreased mechanical properties. In addition, nanomaterials are prone to agglomeration in the polymer matrix, making it difficult to meet high flame retardant grade requirements.

Method used

Phosphorus/boron co-doped graphite phase carbon nitride is used as the core layer, and a copper phytate shell layer is in situ grown on its surface through aqueous solution self-assembly method to construct a core-shell structure, achieving a synergistic flame retardant effect of gas-phase free radical inhibition and condensed phase carbon formation barrier.

Benefits of technology

It significantly improves the carbon residue and thermal stability of the material, enhances the interface compatibility, and achieves a balance between high-efficiency flame retardant properties and mechanical properties. It is suitable for fields such as polymer materials, textiles and coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120737430A_ABST
    Figure CN120737430A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of flame retardance of high polymer materials, and provides a core-shell structure graphite phase carbon nitride derivative and a preparation method thereof.The derivative is prepared by the steps that a precursor containing phosphorus and boron elements is mixed with melamine, and phosphorus / boron co-doped graphite phase carbon nitride is prepared through a high-temperature thermal polymerization reaction; and then assembling the phytic acid copper on the surface of the graphite-phase carbon nitride in an in-situ growth manner by adopting an aqueous solution self-assembly method to construct a derivative with a core-shell structure. The invention provides the graphite phase carbon nitride derivative with the core-shell structure, which is green, environment-friendly, efficient and flame-retardant and simple and convenient in process, and the preparation method of the graphite phase carbon nitride derivative, and the graphite phase carbon nitride derivative has wide application prospect and industrialization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant polymer materials, and in particular relates to a core-shell structured graphite phase carbon nitride derivative and a preparation method thereof. Background Art

[0002] Polymer materials are widely used in a variety of fields, including construction, electrical appliances, transportation, aerospace, and machinery, due to their lightweight, high strength, good toughness, readily available raw materials, low cost, and excellent formability. However, because they are primarily composed of carbon and hydrogen, they are generally highly flammable. To protect people's lives and property, flame-retardant modification of polymer materials is of great significance.

[0003] Traditional flame retardants, typically halogen derivatives (such as bromine and chlorine), offer excellent flame retardancy. However, during combustion, they can release toxic and hazardous gases, such as dioxins, which are highly carcinogenic and bioaccumulative, posing a serious threat to the ecological environment and human health. Consequently, the use of various halogen derivatives, including decabromodiphenyl ether (Deca-BDE), has been banned in most countries.

[0004] Inorganic derivatives are considered environmentally friendly options due to their non-toxicity and pollution-free properties. For example, while aluminum hydroxide has some flame retardancy, it typically requires the addition of more than 40% to meet the UL-94 V-0 standard. This often results in a significant decrease in the material's mechanical properties, limiting its application.

[0005] Nanomaterials have garnered widespread attention in recent years for their ability to significantly enhance flame retardancy and effectively reduce toxic smoke emissions at low addition levels. Graphitic carbon nitride (g-C3N4), a two-dimensional nanomaterial consisting solely of carbon and nitrogen, exhibits excellent thermal stability and resists decomposition at high temperatures. Its layered structure also forms a physical barrier, slowing the diffusion of smoke and combustible gases, demonstrating promising flame retardant potential.

[0006] However, pure g-C3N4 still faces many challenges in practical applications: first, its single physical barrier mechanism makes it difficult to meet the high flame retardant grade requirements (Limiting Oxygen Index LOI <28%); second, its interfacial compatibility with the polymer matrix is ​​poor, and it is prone to agglomeration, affecting the mechanical properties of the material; third, its function is relatively single, and it lacks effective gas-phase flame retardant components, resulting in insufficient ability to suppress initial flames.

[0007] Therefore, developing a new generation of flame retardant system that has multiple flame retardant mechanisms, good interface compatibility, environmental friendliness and high efficiency has become a key issue that needs to be urgently addressed in the current industry. Summary of the Invention

[0008] The object of the present invention is to provide a core-shell structured graphite phase carbon nitride derivative and a preparation method thereof, aiming to solve the problems mentioned in the above background technology.

[0009] The present invention is achieved by providing a core-shell structured graphite phase carbon nitride derivative. The derivative is prepared by mixing a precursor containing phosphorus and boron elements with melamine, and then subjecting the mixture to a high-temperature thermal polymerization reaction to obtain phosphorus / boron co-doped graphite phase carbon nitride. Subsequently, an aqueous solution self-assembly method is used to assemble copper phytate on the surface of the graphite phase carbon nitride in an in-situ growth manner to construct a derivative with a core-shell structure.

[0010] According to a further technical solution, in the phosphorus / boron co-doped graphite carbon nitride, the total mass of phosphorus and boron is 20%-40% of the mass of melamine, and the masses of phosphorus and boron are the same.

[0011] According to a further technical solution, the residual carbon content of the core-shell structure derivative reaches 47.18% at 800°C, a stable chemical bonding interface is formed between the core layer and the shell layer through hydrogen bonding, and the amino groups in the core layer interact with the phosphate groups in the shell layer.

[0012] Another object of the present invention is to provide a method for preparing a core-shell structured graphite phase carbon nitride derivative, comprising the following steps:

[0013] S1: After melamine and phosphorus and boron precursors are fully ground and mixed, they are placed in a muffle furnace for high-temperature calcination;

[0014] S2: grinding and drying the product obtained in step S1 to obtain phosphorus / boron co-doped graphite phase carbon nitride;

[0015] S3: ultrasonically dispersing the material obtained in step S2 in deionized water;

[0016] S4: adding phytic acid to the suspension obtained in step S3, and reacting under heating and stirring conditions;

[0017] S5: After the reaction is completed, the product is filtered and washed with deionized water several times to obtain a phytic acid-coated graphite phase carbon nitride derivative;

[0018] S6: adding copper nitrate trihydrate solution to the product obtained in step S5, and continuing the reaction under heating and stirring conditions;

[0019] S7: After the reaction is completed, the mixture is filtered again, washed with deionized water for multiple times, and dried to finally obtain a graphite phase carbon nitride derivative with a core-shell structure.

[0020] According to a further technical solution, in step S1, the phosphorus-containing precursor is diammonium hydrogen phosphate, the boron-containing precursor is boric acid, and the mass ratio of melamine, diammonium hydrogen phosphate, and boric acid is 1:0.2-0.4:0.2-0.4.

[0021] According to a further technical solution, the mass ratio of melamine, diammonium hydrogen phosphate and boric acid is 1:0.35:0.35.

[0022] According to a further technical solution, in step S1, the high-temperature calcination adopts a gradient temperature increase program: first, keep the temperature at 500°C for 2 hours, then increase the temperature to 550°C at a rate of 1°C / min and keep the temperature for 5 hours.

[0023] According to a further technical solution, in step S3, the ultrasonic dispersion power is 40 kW and the time is 4-10 hours.

[0024] A further technical solution is that in step S4, the reaction temperature for adding phytic acid is 70-90°C, and the reaction time is 1-2 hours; in step S6, the reaction temperature for adding copper nitrate trihydrate solution is 70-90°C, and the reaction time is 2-3 hours; and both steps S4 and S6 are heated in a water bath.

[0025] According to a further technical solution, in steps S4 and S6, the molar ratio of phytic acid to copper ions is 1:2-6.

[0026] The present invention provides a core-shell structure graphite phase carbon nitride derivative and a preparation method thereof, which has the following beneficial effects:

[0027] By co-doping phosphorus and boron elements to create a thermally stable core layer and in situ growing a copper phytate shell on the surface, a synergistic flame retardant effect is achieved through gas-phase free radical suppression and condensed-phase carbonization barrier. This derivative offers advantages such as environmental friendliness, simple preparation, high flame retardant efficiency, and good interfacial compatibility. It effectively addresses the challenges of conventional derivatives, which struggle to balance flame retardancy and environmental friendliness, and the tendency of nanomaterials to agglomerate, leading to decreased mechanical properties. Experiments have shown that the resulting carbon residue is significantly improved, and it exhibits excellent thermal stability and flame retardancy. It is widely applicable in polymer materials, textiles, coatings, and other fields, with promising application prospects and industrial value.

[0028] In summary, the present invention provides a green, environmentally friendly, highly efficient, flame-retardant, and simple-process core-shell structure graphite phase carbon nitride derivative and its preparation method, which has broad application prospects and industrial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 XRD spectra of g-C3N4, PBCN, and PBCN@PACu.

[0030] Figure 2This is the SEM spectrum of g-C3N4.

[0031] Figure 3 This is the SEM spectrum of PBCN.

[0032] Figure 4 This is the SEM spectrum of PBCN@PACu.

[0033] Figure 5 Thermogravimetric curves of the derivatives. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] The specific implementation of the present invention is described in detail below with reference to specific embodiments.

[0036] One embodiment of the present invention provides a core-shell graphite carbon nitride derivative. This derivative is prepared by mixing phosphorus- and boron-containing precursors with melamine and subjecting them to a high-temperature thermal polymerization reaction to produce phosphorus / boron co-doped graphite carbon nitride (PBCN). Subsequently, copper phytate is assembled in situ onto the PBCN surface using a simple and environmentally friendly aqueous solution self-assembly method, creating the core-shell derivative—PBCN@PACu. The combined mass of the phosphorus- and boron-containing precursors is 20%-40% of the mass of the melamine.

[0037] One embodiment of the present invention further provides a method for preparing a core-shell structured graphite phase carbon nitride derivative, comprising the following steps:

[0038] S1: After melamine and phosphorus and boron precursors are fully ground and mixed, they are placed in a muffle furnace for high-temperature calcination;

[0039] S2: grinding and drying the product obtained in step S1 to obtain phosphorus / boron co-doped graphite carbon nitride (PBCN);

[0040] S3: ultrasonically dispersing the material obtained in step S2 (which is beneficial for increasing the specific surface area of ​​the graphite phase carbon nitride derivative and improving the reaction activity) in deionized water;

[0041] S4: adding phytic acid to the suspension obtained in step S3, and reacting under heating and stirring conditions;

[0042] S5: After the reaction is completed, the product is filtered and washed with deionized water several times to obtain a phytic acid-coated graphite phase carbon nitride derivative;

[0043] S6: adding copper nitrate trihydrate solution to the product obtained in step S5, and continuing the reaction under heating and stirring conditions;

[0044] S7: After the reaction is completed, the mixture is filtered again, washed with deionized water for multiple times, and dried to finally obtain a graphite phase carbon nitride derivative with a core-shell structure (PBCN@PACu).

[0045] In step S1, the phosphorus-containing precursor used is diammonium hydrogen phosphate, the boron-containing precursor is boric acid, and the ground mixture of diammonium hydrogen phosphate, boric acid and melamine is first placed in a crucible and then placed in a muffle furnace for high-temperature calcination.

[0046] In step S1, high temperature calcination adopts a gradient temperature rising program, specifically: keeping at 500°C for 2 hours, then heating to 550°C and keeping for 5 hours, with a heating rate of 1°C / min, and naturally cooling to room temperature after high temperature calcination.

[0047] In step S1, the mass ratio of melamine, phosphorus-containing precursor, and boron-containing precursor is 1:0.1-0.2:0.1-0.2, and the masses of the phosphorus-containing precursor and the boron-containing precursor are the same, preferably 1:0.175:0.175.

[0048] In step S3, the ultrasonic dispersion is performed at a power of 40 kW and for a time of 4-10 h.

[0049] In steps S4 and S6, the reaction temperature is controlled between 70-90° C., heated in a water bath, and the reaction time is 1-3 hours. Preferably, the reaction time in step S4 is 1-2 hours, and the reaction time in step S6 is 2-3 hours.

[0050] In steps S4 and S6, the molar ratio of phytic acid to copper ions is 1:2-6, preferably 1:2.

[0051] In addition, in the above scheme, the drying temperature is 60-90°C and the drying time is 8-12 hours.

[0052] Example 1

[0053] The preparation method of a core-shell structure graphite phase carbon nitride derivative comprises the following steps:

[0054] S1: 2g of melamine, 0.4g of diammonium hydrogen phosphate, and 0.4g of boric acid were mixed and ground for 30 minutes. The mixture was then heated to 500°C in a muffle furnace and calcined for 2 hours. The temperature was then raised to 550°C and calcined for 5 hours at a rate of 1°C / min. After cooling to room temperature, the resulting pale yellow block was crushed and ground to obtain graphite carbon nitride. This block was then ultrasonically dispersed in deionized water for 10 hours and dried to obtain graphite carbon nitride derivative nanosheets (PBCN).

[0055] S2: Disperse 0.5g of the nanosheets from step S1 in 200mL of deionized water, pour into a 500mL three-necked flask, and ultrasonically disperse for 30min. Dissolve 0.66g of phytic acid solution in 20mL of deionized water and slowly add it to the three-necked flask using a separatory funnel. Stir at 70°C for 2h. Dissolve 1.45g of copper nitrate trihydrate in 20mL of deionized water to form a copper nitrate aqueous solution, which is added dropwise to the three-necked flask. The molar ratio of phytic acid to copper nitrate is 1:6. Raise the temperature to 80°C and stir continuously for 3h until no yellow-green precipitate forms. Centrifuge the mixed solution at 8000rpm to collect the yellow-green solid, wash it 3-5 times with deionized water, and dry it in a 60°C oven overnight. After crushing and grinding, the yellow-green powder obtained is the core-shell graphite phase carbon nitride derivative (PBCN@PACu).

[0056] Example 2

[0057] The preparation method of a core-shell structure graphite phase carbon nitride derivative comprises the following steps:

[0058] S1: 2g of melamine, 0.2g of diammonium hydrogen phosphate, and 0.2g of boric acid were mixed and ground for 30 minutes. The mixture was then heated to 500°C in a muffle furnace and calcined for 2 hours. The temperature was then raised to 550°C and calcined for 5 hours at a rate of 1°C / min. After cooling to room temperature, the resulting pale yellow block was crushed and ground to obtain graphite carbon nitride. This block was then ultrasonically dispersed in deionized water for 10 hours and dried to obtain graphite carbon nitride derivative nanosheets (PBCN).

[0059] S2: Disperse 0.5g of the nanosheets from step S1 in 200mL of deionized water, pour the mixture into a 500mL three-necked flask, and ultrasonically disperse for 30min. Dissolve 0.66g of phytic acid solution in 20mL of deionized water and slowly add it to the three-necked flask using a separatory funnel. Stir at 70°C for 2h. Dissolve 0.966g of copper nitrate trihydrate in 20mL of deionized water to form a copper nitrate aqueous solution, which is added dropwise to the three-necked flask. The molar ratio of phytic acid to copper nitrate is 1:4. Raise the temperature to 80°C and stir continuously for 3h until no yellow-green precipitate forms. Centrifuge the mixed solution at 8000rpm to collect the yellow-green solid, wash it 3-5 times with deionized water, and dry it in a 60°C oven overnight. After crushing and grinding, the yellow-green powder obtained is the core-shell graphite phase carbon nitride derivative (PBCN@PACu).

[0060] Example 3

[0061] The preparation method of a core-shell structure graphite phase carbon nitride derivative comprises the following steps:

[0062] S1: 2g of melamine, 0.35g of diammonium hydrogen phosphate, and 0.35g of boric acid were mixed and ground for 30 minutes. The mixture was then heated to 500°C in a muffle furnace and calcined for 2 hours. The temperature was then raised to 550°C and calcined for 5 hours at a rate of 1°C / min. After cooling to room temperature, the resulting pale yellow block was crushed and ground to obtain graphite carbon nitride. This block was then ultrasonically dispersed in deionized water for 10 hours and dried to obtain graphite carbon nitride derivative nanosheets (PBCN).

[0063] S2: Disperse 0.5g of the nanosheets from step S1 in 200mL of deionized water, pour the mixture into a 500mL three-necked flask, and ultrasonically disperse for 30min. Dissolve 0.66g of phytic acid solution in 20mL of deionized water and slowly add it to the three-necked flask using a separatory funnel. Stir at 70°C for 2h. Dissolve 0.483g of copper nitrate trihydrate in 20mL of deionized water to form a copper nitrate aqueous solution, which is added dropwise to the three-necked flask in a molar ratio of phytic acid to copper nitrate of 1:2. Raise the temperature to 80°C and continue stirring for 3h until no yellow-green precipitate forms. Centrifuge the mixed solution at 8000rpm to collect the yellow-green solid, wash it 3-5 times with deionized water, and dry it in a 60°C oven overnight. After pulverization and grinding, the yellow-green powder obtained is the core-shell graphite phase carbon nitride derivative (PBCN@PACu).

[0064] The ultrasonic treatments in Examples 1 to 3 were all performed at a power of 40 kW.

[0065] The above embodiments of the present invention provide a core-shell graphite-phase carbon nitride derivative and its preparation method, aiming to address the problems of low efficiency, poor environmental performance, and compromised mechanical properties in traditional flame retardant systems. Furthermore, they overcome technical bottlenecks such as the easy aggregation of nanomaterials in polymer matrices and insufficient thermal stability. Specific advantages are as follows:

[0066] 1) This invention uses water as the sole solvent, and through high-temperature thermal polymerization combined with supramolecular self-assembly technology, the entire preparation process can be completed in just 4-5 hours at 70-80°C. This eliminates the need for toxic or hazardous organic solvents, resulting in mild reaction conditions, low energy consumption, and simple operation. It is suitable for large-scale industrial production, exhibiting excellent environmental friendliness and scalability.

[0067] 2) Through ingenious structural design, this paper constructs a core-shell derivative (PBCN@PACu) composed of a phosphorus / boron co-doped graphitic carbon nitride core and a copper phytate coating as the shell. This structure achieves synergistic flame retardancy through both gas-phase and condensed-phase mechanisms: Copper phytate initially decomposes at 250–350°C, releasing acidic substances that promote carbonization and catalyze cross-linking to form a highly graphitized carbon layer. At 350–450°C, it releases PO· / BO· radicals, interrupting the combustion chain reaction. Simultaneously, the stacking of g-C3N4 sheets forms a dense physical barrier, effectively inhibiting heat transfer and oxygen diffusion. Hydrogen bonding between amino groups (–NH2) in the core and phosphate groups (–PO4³⁻) in the shell forms a stable chemical bond interface, enhancing structural integrity and preventing disintegration and failure at high temperatures. These multiple mechanisms synergistically enhance flame retardancy, resulting in the material exhibiting an excellent limiting oxygen index (LOI) and vertical burning rating (UL-94V-0).

[0068] 3) For the first time, copper phytate was combined with element-doped g-C3N4, resulting in a synergistic effect. Experimental data showed that pure g-C3N4 had a carbon residue of only 3.24% at 800°C; this increased to 37.02% for the phosphorus / boron-doped g-C3N4 derivative. Further coating with copper phytate resulted in a maximum carbon residue of 47.18%, demonstrating a significant synergistic effect between the two, significantly enhancing the material's refractory properties and thermal stability.

[0069] 4) Through surface functionalization modification, the present invention effectively improves the interfacial compatibility of g-C3N4 nanosheets in the polymer matrix, avoiding the common agglomeration problem of nanomaterials, thereby maintaining or even optimizing the mechanical properties of the material while improving the flame retardant performance, achieving the dual goals of flame retardancy and reinforcement.

[0070] 5) This derivative can be widely used in polymer materials (such as polypropylene, epoxy resin, polyurethane), textiles, coatings and other fields. It is especially suitable for high-end flame retardant application scenarios with high requirements for environmental protection and comprehensive performance. It has good industrialization prospects and market promotion value.

[0071] In summary, the core-shell structured graphite phase carbon nitride derivatives and their preparation methods provided by the present invention not only solve the problems of low efficiency, poor environmental protection, and poor dispersibility of a single flame retardant mechanism, but also have significant innovation and practicality in structural design, functional integration, performance improvement, etc., filling the technical gap in related fields.

[0072] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0073] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.

Claims

1. A core-shell structure graphite phase carbon nitride derivative, characterized in that: The derivative is prepared by mixing a precursor containing phosphorus and boron elements with melamine and performing a high-temperature thermal polymerization reaction to obtain phosphorus / boron co-doped graphite phase carbon nitride; Subsequently, the aqueous solution self-assembly method was used to assemble copper phytate on the surface of graphite phase carbon nitride in an in situ growth manner to construct a derivative with a core-shell structure.

2. The core-shell graphite phase carbon nitride derivative according to claim 1, characterized in that: In the phosphorus / boron co-doped graphite carbon nitride, the total mass of phosphorus and boron is 20%-40% of the mass of melamine, and the masses of phosphorus and boron are the same.

3. The core-shell graphite phase carbon nitride derivative according to claim 2, characterized in that: The residual carbon content of the core-shell structure derivative reaches 47.18% at 800°C, a stable chemical bonding interface is formed between the core layer and the shell layer through hydrogen bonding, and the amino groups in the core layer interact with the phosphate groups in the shell layer.

4. A method for preparing a core-shell graphite phase carbon nitride derivative according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: After melamine and phosphorus and boron precursors are fully ground and mixed, they are placed in a muffle furnace for high-temperature calcination; S2: grinding and drying the product obtained in step S1 to obtain phosphorus / boron co-doped graphite phase carbon nitride; S3: ultrasonically dispersing the material obtained in step S2 in deionized water; S4: adding phytic acid to the suspension obtained in step S3, and reacting under heating and stirring conditions; S5: After the reaction is completed, the product is filtered and washed with deionized water several times to obtain a phytic acid-coated graphite phase carbon nitride derivative; S6: adding copper nitrate trihydrate solution to the product obtained in step S5, and continuing the reaction under heating and stirring conditions; S7: After the reaction is completed, the mixture is filtered again, washed with deionized water for multiple times, and dried to finally obtain a graphite phase carbon nitride derivative with a core-shell structure.

5. The method for preparing a core-shell graphite phase carbon nitride derivative according to claim 4, characterized in that: In step S1 , the phosphorus-containing precursor is diammonium hydrogen phosphate, the boron-containing precursor is boric acid, and the mass ratio of melamine, diammonium hydrogen phosphate, and boric acid is 1:0.2-0.4:0.2-0.

4.

6. The method for preparing a core-shell graphite phase carbon nitride derivative according to claim 5, characterized in that: The mass ratio of the melamine, diammonium hydrogen phosphate and boric acid is 1:0.35:0.

35.

7. The method for preparing a core-shell graphite phase carbon nitride derivative according to claim 4, characterized in that: In step S1, the high temperature calcination adopts a gradient temperature increase program: The temperature was first kept at 500 °C for 2 hours, then increased to 550 °C at a rate of 1 °C / min and kept at this temperature for 5 hours.

8. The method for preparing a core-shell graphite phase carbon nitride derivative according to claim 4, characterized in that: In step S3, the ultrasonic dispersion is performed at a power of 40 kW and for a time of 4-10 hours.

9. The method for preparing a core-shell graphite phase carbon nitride derivative according to claim 4, characterized in that: In step S4, the reaction temperature for adding phytic acid is 70-90°C and the reaction time is 1-2 hours; In step S6, the reaction temperature of adding copper nitrate trihydrate solution is 70-90° C. and the reaction time is 2-3 hours; Furthermore, both step S4 and step S6 adopt a water bath heating method.

10. The method for preparing a core-shell graphite phase carbon nitride derivative according to claim 4, characterized in that: In steps S4 and S6, the molar ratio of phytic acid to copper ions is 1:2-6.

Citation Information

Patent Citations

  • Anti-bacterial flame-retardant polycaprolactone film, and preparation method thereof

    CN110330678A

  • LDHs@PA-Cu (II) / PLA composite film and preparation method thereof

    CN110408183A

  • Preparation method and application of flame-retardant unsaturated polyester resin composite material containing carbon nitride nano hybrid

    CN111117180A

  • Photocatalytic methane conversion material and preparation method thereof

    CN115805090A

  • Flame-retardant aluminum honeycomb panel and preparation method thereof

    CN118306072A

Cited By

  • Composite negative electrode material doped with nitrogen / phosphorus / boron elements and preparation process of composite negative electrode material

    CN121894653A

  • Composite negative electrode material doped with nitrogen / phosphorus / boron elements and preparation process thereof

    CN121894653B

  • Flame-retardant composite material based on synergistic enhancement of talc and graphene lamellas and application of flame-retardant composite material

    CN122278054A